AL-Isfahaniï¿½s fandom in the Kitab al-A?ani (the book of songs): an analysis of the biography of Ibn Suray? - Su, I-Wen (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article examines the biography of the musician, Ibn Suray? (d. c. 96/714), in the Kit?b al-A??n?, with regard to how the compiler, Ab? al-Fara? ?Al? b. al ?usayn al-I?fah?n? (d. after 356/967), edits his source material (a?b?r) in order to articulate his admiration for the musician, Is??q b. Ibr?h?m al-Maw?il? (155 235/772ï¿½850). Through an investigation of al-I?fah?n?ï¿½s repetition and juxtaposition of a?b?r, his fandom is revealed in the article on Ibn Suray?, where al-I?fah?n? shapes the narrative that problematizes a report unfavourable towards Is??q while elevating his musical achievement. Although the Kit?b al-A??n?, as an a?b?r compilation, seems void of authorial voice, and, thus, of originality, examination of the compilerï¿½s editorial work shows his articulation of his own perspective.